Role of community figure in Healthy Indonesia Program with family approach (PIS-PK) in Banjarnegara District, Central Java - Mujiati Mujiati; Eva Sulistiowati; Siti Nurhasanah (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
The involvement of community figure is one form of participation in health development, including in the Healthy Indonesia Program with Family Approach (PIS-PK). The purpose of this study was to determine the role of community figure in PIS-PK. The type of study was a qualitative study in one kelurahan which was included in the working area of Community Health Care (CHC) Banjarnegara 1 in Banjarnegara District, Central Java, which was chosen purposively. Data collection was done by in-depth interview. The key informants were community figure, namely from the kelurahan (kelurahan head and its staff) and community members who were considered community figure in the village. Data triangulation was done by conducting in-depth interview with the head and staff of community health centre and the community. Data that has been obtained was analyzed thematically. The results of the study showed that community figure played an important role in the implementation of PIS-PK as sources of information about PIS-PK, helping field organizing, helping prepare complete families documents, assisting CHC staff and surveyor in home visits and helping solve problems that arise, and generally playing a role in the smooth implementation of PIS-PK. Social support from the local government and communities can be a motivation to continue to play a role in supporting the success of PIS-PK.